The Impact of COVID-19 on Global Higher Education - Marinoni, Giorgio; van’t Land, Hilligje (International Higher Education, 2020)
The COVID-19 pandemic is having an enormous impact on higher education. In many countries around the world, campuses are closed and teaching has moved online. Internationalization has slowed down considerably. Despite these challenges, HEIs have reacted positively, often implementing new solutions to continue providing teaching, research, and service to society .